Drifting Electron Holes Occurring During Geomagnetically Quiet Times: BD‐IES Observations. Issue 11 (14th November 2019) - Liu, Z.‐Y.; Zong, Q.‐G.; Zou, H.; Wang, Y. F.; Wang, B.
Abstract: Drifting electron holes (DEHs), manifesting as sudden but mild dropout in electron flux, are a common phenomenon seen in the Earth's magnetosphere. It manifests the change of the state of the magnetosphere. However, previous studies primarily focus on DEHs during geomagnetically active time (e.g., substorm). Not until recently have quiet time DEHs been reported. In this paper, we present a systematic study on the quiet time DEHs. BeiDa Imaging Electron Spectrometer (BD‐IES) measurements from 2015 to 2017 are investigated. Twenty‐two DEH events are identified. The DEHs cover the whole energy range of BD‐IES (50–600 keV). Generally, the DEHs are positively dispersive with respect to energy. Time‐of‐flight analysis suggests the dispersion results from electron drift motion and gives the location where the DEHs originated from. Statistics reveal the DEHs primarily originated from the postmidnight magnetosphere. In addition, superposed epoch analysis applied to geomagnetic indices and solar wind parameters indicates these DEH events occurred during geomagnetically quiet time. No storm or substorm activity could be identified. However, an investigation into nightside midlatitude ground magnetic records suggests these quiet time DEHs were accompanied by Pi2 pulsations. The DEH‐Pi2 connection indicates a possible DEH‐bursty bulk flow (BBF) connection, since nightside midlatitude Pi2 activity is generally attributed to magnetotail BBFs. This connection is also supported by a case study of coordinated magnetotail observations from Magnetospheric Multiscale spacecraft. Therefore, we suggest the quiet time DEHs could be caused by magnetotail BBFs, similar to the substorm time DEHs. Key Points: Twenty‐two drifting electron hole (DEH) events during geomagnetically quiet time were identified from 2‐year BD‐IES measurement The DEHs initially occur in the postmidnight magnetosphere, then drift with electrons, and are dispersed by the drift Given a negative phase space density radial gradient, electron inward transport induced by bursty bulk flow results in the DEHs